1994
DOI: 10.1016/0304-3959(94)90135-x
|View full text |Cite
|
Sign up to set email alerts
|

On the absence of correlation between responses to noxious heat, cold, electrical and ischemie stimulation

Abstract: Is a person's response to one noxious stimulus similar to his/her responses to other noxious stimuli? This long-investigated topic in pain research has provided inconclusive results. In the present study, 2 samples were studied: one using 60 healthy volunteers and the other using 29 patients with coronary artery disease. Results showed near-zero correlations between measures of heat, cold, ischemic, and electrical laboratory pains, as well as between these laboratory pains and an idiopathic pain, the latency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 22 publications
4
56
0
Order By: Relevance
“…No correlation was found to CPT tolerance. In other words, clamp pain intensity correlated to other QST to varying degrees, which is in line with the literature which suggests, that different methods of QST measure different aspects of pain sensitivity and modulation [6,7,18,19].…”
Section: Correlationsupporting
confidence: 90%
“…No correlation was found to CPT tolerance. In other words, clamp pain intensity correlated to other QST to varying degrees, which is in line with the literature which suggests, that different methods of QST measure different aspects of pain sensitivity and modulation [6,7,18,19].…”
Section: Correlationsupporting
confidence: 90%
“…However, as Janal et al (1994) note, findings obtained using a specific pain modality have not always generalised to other pain modalities. Indeed, pain ratings compared across noxious stimuli such as cold pressor, heat, electrical and pressure pain responses have often demonstrated weak or even no correlation (Davidson and McDougall, 1969;Lynn and Perl, 1977;Janal et al, 1994). Furthermore, Riley et al (1998) found that while sex differences in pain tolerance were large for pressure pain, they were often small to moderate for noxious heat stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…5,50,51 This is not a new finding, as there is low to moderate correlation across different pain stimuli when examined on the same individual. 34,36 However, this is important to recognize, as many prior studies 15,17,18,[20][21][22]31 that have reported on side-to-side comparisons utilized only a single type of stimulus. It is possible that individuals exhibit different patterns of experimental pain sensitivity, based on the stimuli used for testing.…”
mentioning
confidence: 99%